Research Progress and Trend Analysis of Picking Technology for Korla Fragrant Pear - Yanwu Jiang; Jun Chen; Zhiwei Wang; Guangrui Hu (Horticulturae)
This article provides a comprehensive review of the current results of pear-picking technology, delving into the development process, classification, application status, and development trends of picking machinery, picking robots, and intelligent technology. By analyzing the key technologies in pear fruit harvesting, this paper explores the working principles of harvesting machinery, the technical characteristics of harvesting robots, and the potential applications of intelligent technology. Furthermore, a bibliometric analysis was employed to examine two decades of the research literature on Korla fragrant pear, spanning from January 2004 to June 2024, utilizing the core collection of the Web of Science and the China National Knowledge Infrastructure database as the retrieval platforms. The visualization of the analysis results indicates that the focal points of research in this field are predominantly aspects such as the quality and storage conditions of fragrant pears, with a scarcity of studies directed toward mechanized harvesting. Additionally, this study addresses the existing challenges and issues within pear-picking technology and delineates potential avenues for future development, with the objective of providing a foundation for subsequent research on Korla fragrant pear-harvesting technology.